2022
DOI: 10.1007/s15010-022-01952-2
|View full text |Cite
|
Sign up to set email alerts
|

Plasmodium cynomolgi in humans: current knowledge and future directions of an emerging zoonotic malaria parasite

Abstract: Plasmodium cynomolgi ( Pcy ), a simian malaria parasite, is a recent perfect example of emerging zoonotic transfer in human. This review summarizes the current knowledge on the epidemiology of natural Pcy infections in humans, mosquitoes and monkeys, along with its biological, clinical and drug sensitivity patterns. Knowledge gaps and further studies on Pcy in humans are also discussed. This parasite currently seems to be geographi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 93 publications
(96 reference statements)
0
6
0
Order By: Relevance
“…LM is the standard and reports pinpointed that Po and Pm infections are misdiagnosed as Pv and Pf infections using LM in the country ( 124 , 125 ). It is worth determining the extent and characterizing these species in MiP as previous studies showed their ability to elicit SM and noted pathophysiological differences between P. ovale curtisi and P. ovale wallikeri ( 4 , 126–129 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…LM is the standard and reports pinpointed that Po and Pm infections are misdiagnosed as Pv and Pf infections using LM in the country ( 124 , 125 ). It is worth determining the extent and characterizing these species in MiP as previous studies showed their ability to elicit SM and noted pathophysiological differences between P. ovale curtisi and P. ovale wallikeri ( 4 , 126–129 ).…”
Section: Resultsmentioning
confidence: 99%
“…This burden has significantly increased compared to previous years, partially due to the current COVID-19 pandemics ( 2 , 3 ). Malaria is due to five Plasmodium species that are transmitted to human through infecting bites of female Anopheles mosquitoes ( 4 ). Plasmodium falciparum ( Pf ) and Plasmodium vivax ( Pv ) are the predominant malaria species around the world; Pf is the most severe and dangerous species while Pv is the most geographically spread but can also induce severe clinical attacks ( 5 , 6 ).…”
Section: Introductionmentioning
confidence: 99%
“…The majority of symptomatic infections result in mild febrile cases of uncomplicated malaria (UM), as severe disease only occurs in 1-2% of all cases 2 . Out of the eight Plasmodium spp that have been reported to cause either direct or zoonotic infection in humans, P. falciparum is considered a major driver of severe disease and mortality 3,4 . Cerebral malaria (CM) is a severe neurological complication of malaria infection that is a major cause of death, with mortality estimated between 15-25% and clinical manifestations including unarousable coma and seizures 5,6 .…”
Section: Introductionmentioning
confidence: 99%
“…Although pathogenicity in crab-eating macaques is less consistent than in rhesus macaques, these monkeys still variably develop severe symptoms and clinical presentation in response to P. coatneyi 20 . In contrast, P. cynomolgi has been found to naturally infect a range of primate hosts in Southeast Asia, including various macaque species 26 . Alongside the established simian zoonotic P. knowlesi , both P. cynomolgi 4, 2730 and P. coatneyi 30 parasites were recently found in blood samples of humans, though the latter appears to be far rarer, as supported by prior failed attempts to experimentally infect people 31 .…”
Section: Introductionmentioning
confidence: 99%